The Impact Of Ambidextrous Knowledge Capabilities, Supply Chain Management Skills, Coping Capacity And Moderated By Emotional Intelligence Towards Decision-Making Competence - Khor, Lay Kheng (2024)
The most recent global pandemic outbreak have created a huge global crisis in breaking down many global supply chains whereby the Malaysian manufacturers were caught in the global chip crisis. Decision-makers are faced with very challenging position as the application of supply chain resilience mechanisms may be questionable and unreliable in the supply chain resilience surrounding. As a result, decision-makers in the Malaysian manufacturing companies are very much impacted as they have to continue to learn new ways to cope, adapt and mitigate the risk to navigate through the uncertainties ahead of them. This implies that the knowledge, skills, abilities and competencies of these decision-makers have become the centre stage for organizations’ survival and sustainability. The main objective of this study is to examine the relationship between ambidextrous knowledge capabilities, supply chain management skills, coping capacity and emotional intelligence that influence decision-making competence in the supply chain resilience environment in the manufacturing companies of Malaysia through the integration of the behavioural decisional theory and competency model. The research gaps and theoretical framework with respect to the construct of decision-making competence are elaborated.